Poland"s Competitive Position in Trade in Agri-Food Products with the United Kingdom – Selected Aspects - Łapińska, Justyna; Graszewicz, Maurycy; Zdunek-Rosa, Ewa (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2017)
Thirteen years have passed since Poland's accession to the European Union. This is a period long enough to make some generalisations over the accession results. This paper focuses on assessing the competitive position of Poland in trade in agri-food products with one of its most important trading partners – the United Kingdom. For this purpose, quantitative indexes of competitive positioning were used, in particular, the trade coverage ratio as well as the revealed comparative advantage indexes – RCAi and LFIi. The conducted analyses show that Poland's competitive position in agri-food trade with the United Kingdom improved markedly over the period considered. The dynamic growth in trade, especially in exports, a significant increase in the trade balance surplus, and generally favourable comparative advantage indexes for Poland show that the period of EU membership has been well utilised by Polish food producers. Polish food is increasingly eagerly bought by demanding British consumers.